Methods for Developing Marketing Programs in the Context of the Formation of Clusters of Textile Enterprises - Musayeva Shoira Azimovna (International Journal on Economics, Finance and Sustainable Development, 2021)
The article examines the experience of creating textile clusters, and also examines the content of the marketing programs of enterprises. Industrial clusters are primarily able to withstand competition within this sector in local and global markets. The cluster theory entered the scientific process in the form of a marketing strategy, as an idea-method that allows enterprises of the state, regions and regions to win in a competitive environment in the market.